MICRO ROLE PLAYING METHOD FOR EMPATHY OF CHILDREN AGED 5-6 YEARS - Diana Anisa Nurhasanah; Siti Wahyuningsih; Ruli Hafidah (Universitas Sebelas Maret, 2020)
This study aims to determine the effect of using the micro role playing method on empathy for children 5-6 years. This research is a quantitative research with Quasi Experimental Design in the form of Nonequivalent Control Group. The study was conducted from April to December 2018. Sampling using saturated samples. The research sample of 36 children was taken from the Dharma Wanita 1 Banaran Kindergarten and Banaran Kindergarten, Kalijambe, Sragen. The technique of collecting data uses observation, interviews and documentation. The validity of the instrument uses expert judgment which is then tested by the instrument. Data analysis consisted of prerequisite tests and hypothesis testing. The prerequisite test in data analysis consisted of a normality test and a homogeneity test, while a hypothesis test used an independent sample t-test. The prerequisite test results show normal and homogeneous data. The results of the hypothesis test show that the difference in the average value of the posttest value of the experimental group and the control group is 24.33 and 20.33 with a significance value of 0.000 <0.05. While the difference in the value of the pretest and posttest in the experimental group was 18.39 to 24.33. The conclusion of the study shows that there is an influence of the use of the micro role playing method on empathy for children aged 5-6 years.